Co-designing to advance community health and health equity in Wisconsin: Building the Neighborhood Health Partnerships Program. Issue 1 (18th February 2021) - Bonham-Werling, Jessica; Passmore, Susan; Hendricks, Korina; Bednarz, Lauren; Faust, Victoria; Talaga, Alan; Smith, Maureen
Abstract: Engaging communities can increase the speed of translating health and health equity research into practice. Effective engagement requires a shared understanding of the health of a community. This can be challenging without timely and accurate local health data, or ways to provide that data, that are directly applicable to improving community health outcomes. The University of Wisconsin Institute for Clinical and Translational Research formed the Neighborhood Health Partnerships Program (NHP) to overcome this challenge, making sub-county health data available to researchers and community stakeholders while incorporating community voice into data delivery processes. The NHP team used a human-centered design approach to facilitate community engagement. Through co-design, the team created NHP reports and data-to-action tools to maximize accessibility and utility for a diverse set of community stakeholders. Early indicators show that the final co-designed NHP reports and data-to-action tools will be immediately useful in promoting community–academic partnerships and in planning, implementing, and evaluating research and other initiatives in communities. The NHP program demonstrates that an effective co-design strategy can lead to increased usability and adoption of Clinical and Translational Science Award resources, enabling a shared understanding of community health and ultimately leading to the successful translation of research into practice.